Seismic stratigraphy and development of a modern isolated carbonate platform (Xuande Atoll) in the South China Sea - Liu, Y.; Wu, S.; Li, X.; Chen, W.; Han, X.; Yang, C.; Qin, Y.; Huang, X.; Yang, Z.; Sun, J.; Zhu, L. (Frontiers in Earth Science, 2023)
Xuande Atoll is an isolated carbonate platform that has developed since the early Miocene. This study conducted high-resolution seismic surveys and shallow drilling to understand its internal structure and development. Five seismic sequences were observed (from bottom to top): SQ1 (early Miocene), SQ2 (middle Miocene), SQ3 (late Miocene), SQ4 (Pliocene), and SQ5 (Quaternary). The seismic data indicated that the platform formation started in the early Miocene and flourished during the early and middle Miocene. The platform shrank before the isolated platform formed in the middle Miocene. The final shrinking stage occurred in the southern and western parts of the platform at the end of the Miocene, which may reflect rapid tectonic subsidence and increased terrigenous sediment inputs owing to the formation of the semi-marginal sea. The peri-platform contains a falling sea-level sequence that was dominated by mass wasting deposits.